NKG2D triggering hampers DNAM-1-mediated signaling in human NK cells - Marangio, Caterina; Milito, Nadia Domenica; Putro, Erisa; Carnevale, Alessia; Capuano, Cristina; Zingoni, Alessandra; Cippitelli, Marco; Santoni, Angela; Paolini, Rossella; Molfetta, Rosa (Frontiers in Immunology, 2025)
IntroductionNatural Killer (NK) cells are cytotoxic innate lymphocytes able to detect transformed cells through the balanced action of inhibitory and activating receptors. NKG2D is one of the main activating receptors involved in tumor surveillance thanks to its ability to recognize stress-induced ligands. Of note, the prolonged exposure to NKG2D ligands promotes receptor down-modulation that results in defective activation of NKG2D and other unrelated activating receptors, including DNAM-1 that is also involved in tumor clearance. However, further investigations are necessary to characterize how the NKG2D/DNAM-1 interplay affects NK cell anti-tumor function.MethodsPrimary cultured human NK cells were stimulated with the natural ligand MICA or an anti-NKG2D agonist antibody. The expression of activating and inhibitory receptors as well as DNAM-1-triggered signaling events and cytotoxicity were evaluated by flow cytometry. DNAM-1-mediated granule polarization was evaluated by confocal microscopy.ResultsWe showed that NKG2D crosslinking mediated by the natural ligand MICA or an agonist antibody had different consequences on primary cultured human NK cells. Indeed, MICA stimulation increases the expression of the checkpoint receptor TIGIT that is able to counteract DNAM-1 activation. Stimulation with the agonist antibody, without altering TIGIT expression, directly inhibits DNAM-1-mediated signal transduction and cytotoxic function with a mechanism that required NKG2D endocytosis.DiscussionOur findings contribute to shed light on the functional consequences of NKG2D engagement, demonstrating that a direct impact on DNAM-1-mediated signal transduction occurs independently from the modality of NKG2D crosslinking. Understanding the molecular mechanisms responsible for suppression of NK cell activation may help the development of therapeutic anti-cancer strategies aimed to prevent NK cell dysfunction or to reinvigorate an impaired cytotoxic activity.